Tinjauan Yuridis Tentang Implementasi Prinsip Pancasila Sebagai Landasan Politik Di Indonesia - Ria Ermina Purba; Risa Amalia; Danugrah Akbar (Universitas Sains dan Teknologi Komputer, 2024)
Pancasila has been the main political foundation in Indonesia since its independence in 1945. The implementation of Pancasila principles in state politics has been the subject of important juridical debate. This article investigates the juridical review of the implementation of the Pancasila principles as a political foundation in Indonesia. Through analysis of the constitution, court decisions, and academic discussions, this research explores how the principles of Pancasila are understood, interpreted, and applied in the Indonesian political context. The results of this research provide an in-depth understanding of the role and relevance of Pancasila in the formation of public policy and the protection of human rights in Indonesia. Pancasila, as the foundation of the Indonesian state, has a very important role in determining the direction of state political policy. The implementation of Pancasila principles as a political foundation has become a significant debate in the juridical context in Indonesia. This research aims to conduct an in-depth review of the implementation of Pancasila principles in Indonesian political policy juridically.